Microfresamento do titânio comercialmente puro com as trajetórias de usinagem convencional e trocoidal - Anderson Júnior dos Santos (2023)
Commercially pure titanium and its alloys have been growing researched due to their specific strength, biocompatibility, and corrosion resistance. ASTM F67 grade 4 (TC4) commercially pure titanium is commonly used in the manufacturing of orthopedic and dental implants. However, it is considered a difficult-to-machine material due to its low thermal conductivity, which produces high temperatures in the cutting zone, consequently prematurely wearing out the cutting tool. In this context, the aim of this work is to analyze the influence of input parameters, such as tooth feed rate (fz ), machining depth (ap), tool diameter, as well as conventional (TUC) and trochoidal (TPC) machining paths, on machining force, acoustic emission (AE) signals, surface quality, width, and top burr height during the micromilling of TC4 using solid carbide micro end mills coated with titanium aluminum nitride TiNAl with diameters of ϕ 500 and ϕ 800 μm were used. The micro end mills were characterized by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The micro milled slots were characterized by SEM and contact profilometry. The characterization of the micro end mills before micromilling tests showed evidence of non-uniformity of the TiNAl coating on the cutting edge of the micro end mills. It was observed that the magnitude of the force signals in the Fy direction increased when using the TUC path. However, for forces in the Fx and Fz directions, the signal intensity increased when employing the TPC path. The AE signals showed an increasing trend for higher fz and ap values during micromilling with the TUC path. Regarding the surface response, the improvement of surface quality occurred for smaller fz , ap, and TUC path. Increasing fz and ap resulted in larger top burrs when using the TUC path. In this context, it is important to note that the proper selection of machining parameters can significantly influence the quality of parts in micromilling of TC4. Therefore, the results obtained in this study can contribute to the development of more efficient and economical techniques for micromilling of TC4.